Variants in the superior attachment of uncinated process and their corresponding frontal sinus drainage pattern: a computed tomography-based retrospective clinical study - M. G. A., Visali; Ravichandran, Praveen; Balasubramani, Naveen Kumar; Ayyadurai, Saranya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Understanding the morphology and spatial relationships of the uncinate process and its associated spaces is crucial for diagnosing and treating conditions affecting sinus drainage and ventilation. This consistent anatomical structure is an important surgical landmark for endoscopic sinus surgery. Methods: Computed tomography (CT) records of 100 patients over two years were extracted via the hospital's PACS system. The type of superior insertion of uncinate process (UP) was observed in coronal cuts of CT scan images, and classification was done based on the Friedmann and Landsberg classification system and tabulated. The corresponding variations in the frontal sinus outflow tract were noticed, and their effect on frontal sinusitis was recorded. Sinusitis of the frontal sinus was in guidance with EPOS 2020 (mucosal changes within the ostiomeatal complex or sinus). Results: Type 2 was the most common of uncinate attachments (39.5%). The least common variant was type 5 (4%). Medial-type frontal sinus drainage pathway was observed in 78.5% of patients. Sinusitis was present in 23.5% of our study population. Type 2 had a 25% contribution to the occurrence of sinusitis. The medial frontal sinus drainage pathway contributes 24% to sinusitis with a significant p value of 0.010. Conclusions: Uncinate process, with its varying superior attachment, influences the frontal sinus outflow tract and may contribute to the development of frontal sinusitis. Awareness of the possible variations in the attachment of the uncinate process is vital in the preoperative planning process, which will serve as a road map to surgeons and aid in preparedness for intraoperative complications.